Factor XIII Deficiency and Intracranial Bleed: Surgical Management and Prophylaxis with Cryoprecipitate - Furtado, Sunil V.; Hegde, Pranoy; Palassery, Rasmi; Karunakara, B. P. (Journal of Pediatric Neurology, 2021)
Factor XIII (FXIII) deficiency is a rare bleeding disorder with affected patients having high propensity for intracranial hemorrhage. A 12-year-old girl presented with severe headache, limb weakness, and rapidly worsening sensorium over 4 days. Magnetic resonance imaging of the brain and computed tomography (CT) of the head showed intraparenchymal bleed. Patient had normal coagulation profile and abnormal FXIII level. The perioperative management included cryoprecipitate transfusion to bring the FXIII value to 74%. She underwent craniotomy and evacuation of the hematoma. Postoperatively, she received prophylaxis against rebleed with cryoprecipitate. In the absence of FXIII concentrate, correction of FXIII deficiency is possible with cryoprecipitate in emergent situations.
Keywords: brain; craniotomy; cryoprecipitate; factor XIII deficiency; intraparenchymal bleed